Evolution of the JULGI–SMXL4/5 module for phloem development in angiosperms - Chanyoung Park; Hyun Seob Cho; Yookyung Lim; Chung Hyun Cho; Hoyoung Nam; Sangkyu Choi; Hojun Lim; Young-Dong Kim; Hwan Su Yoon; Hyunwoo Cho; Ildoo Hwang (Proceedings of the National Academy of Sciences, 2025)
Bifacial cambium, which produces xylem and phloem, and monopodial architecture, characterized by apical dominance and lateral branching from axillary buds, are key developmental features of seed plants, consisting of angiosperms and gymnosperms. These allow seed plants to adapt to diverse environments by optimizing resource allocation and structural integrity. In seed plants, SUPPRESSOR OF MAX2-LIKE ( SMXL ) family members function in phloem development and strigolactone-induced inhibition of axillary bud outgrowth. Although strigolactone signaling regulates most SMXL family members, the only known regulator of SMXL4 and SMXL5 is the RNA-binding protein JULGI. We demonstrate that in angiosperms, by directly regulating SMXL4/5 expression, JULGI uncouples SMXL4/5 activity from strigolactone signaling. JULGI and ancestral SMXL s from seedless vascular plants or SMXL4/5 from seed plants are coexpressed in the phloem tissues of vascular plants, from lycophytes to angiosperms. Core angiosperm SMXL4/5 mRNAs contain a G-rich element in the 5′ untranslated region (UTR) that serves as a target sequence for JULGI to negatively regulate SMXL4/5 expression. Heterologous expression of JULGI s from various angiosperms rescued the Arabidopsis jul1 jul2 mutant. Expressing SMXL4/5 s from seed plants and ancestral SMXL s rescued Arabidopsis smxl4 smxl5 . Angiosperm SMXL4/5s lack an RGKT motif for proteasomal degradation. Indeed, treatment with the synthetic strigolactone analog rac -GR24 induced proteasomal degradation of SMXL from ferns and SMXL5a from gymnosperms, but not SMXL4/5 from angiosperms. These findings suggest that in ancestral angiosperms, the 5′ UTR of SMXL4/5 gained G-rich elements, creating a regulatory module with JULGI that allows the phloem development pathway to act independently of strigolactone signaling.